Anger, anger expression, alcohol, and alcohol consequences - Carter, Lana L., author; Deffenbacher, Jerry L., advisor (Colorado State University. Libraries, 2002)
This study investigated the relationship of anger, anger expression styles, alcohol consumption and alcohol-related consequences. The results show alcohol consumption and intoxication are prevalent behaviors among college students. Although males reported drinking and becoming intoxicated more often than females, gender was not a strong predictor of frequency of alcohol consequences. However, gender was of greater predictive power in accounting for alcohol-related consequences in the worst-case incident, with males suffering more consequences than females. Trait anger was significantly related to the total alcohol consequences, worst alcohol-related incidents, and to alcohol-related behavioral consequences (e.g. aggressive behaviors). Prosocial anger expression styles and anger control were inversely related to negative alcohol-related consequences and total consequences. Anger expression styles such as verbal putdowns and verbal assaults were related to alcohol consequences. Anger and anger expression styles played a significant role in predicting the worst alcohol-related event. Intoxication played the greatest role in predicting physical consequences, total frequency of consequences, and aggressive behaviors towards others. Results were discussed in terms of the importance of addressing anger management issues in alcohol treatment and prevention programs.
Keywords: psychotherapy; behavioral sciences; behavioral psychology; clinical psychology